2005
DOI: 10.1111/j.1075-122x.2005.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Adenoma of the Breast

Abstract: A 59-year-old woman presented with a subareolar mass of the left breast. The lesion was described as firm in consistency; examination with mammography and sonography identified a 2 cm lobulated mass with irregular margins (Figs 1 and 2). Ultrasound-guided fine-needle aspiration (FNA) cytology revealed the presence of laminar aggregates of epithelial elements with elongated and polymorphic nuclei. Other features included the presence of myxoid tissue containing spindle cells and fragments of cartilaginous strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The mammographic fi ndings have been reported in 11 articles. [9][10][11][12][13][14][15][16][17][18][19] The ultrasonography also has been reported in only 2 articles. 16,19 Because of its extreme rarity in the breast and of imaging fi ndings often suggestive of carcinoma, a correct preoperative diagnosis might be diffi cult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6][7][8] The mammographic fi ndings have been reported in 11 articles. [9][10][11][12][13][14][15][16][17][18][19] The ultrasonography also has been reported in only 2 articles. 16,19 Because of its extreme rarity in the breast and of imaging fi ndings often suggestive of carcinoma, a correct preoperative diagnosis might be diffi cult.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] The ultrasonography also has been reported in only 2 articles. 16,19 Because of its extreme rarity in the breast and of imaging fi ndings often suggestive of carcinoma, a correct preoperative diagnosis might be diffi cult. Many authors have reported that preoperative diagnosis was carcinoma, [9][10][11][12][13] whereas benign tumors were suspected in three cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pleomorphic adenoma is one such benign tumor found commonly in the salivary glands but rarely in the breast and skin. Seventy‐one cases of pleomorphic adenoma of the breast (PAB) have been reported in literature with two being recurrent (1–6). The correct diagnosis has most often been made postoperatively and in a few cases misdiagnosis as malignancies has resulted in erroneous mastectomies (2).…”
Section: Introductionmentioning
confidence: 99%